A Permselective CeOx Coating To Improve the Stability of Oxygen Evolution Electrocatalysts. (5th January 2018) - Obata, Keisuke; Takanabe, Kazuhiro
Abstract: Highly active NiFeO x electrocatalysts for the oxygen evolution reaction (OER) suffer gradual deactivation with time owing to the loss of Fe species from the active sites into solution during catalysis. The anodic deposition of a CeO x layer prevents the loss of such Fe species from the OER catalysts, achieving a highly stable performance. The CeO x layer does not affect the OER activity of the catalyst underneath but exhibits unique permselectivity, allowing the permeation of OH − and O2 through while preventing the diffusion of redox ions through the layer to function as a selective O2 ‐evolving electrode. The use of such a permselective protective layer provides a new strategy for improving the durability of electrocatalysts.